Designing a Moral Distress Questionnaire in Occupational Therapists and Evaluating Its Face and Content Validities - Masoumeh Khaleghi; Minoo Kalantari; Mehdi Rezaei; Alireza Akbarzadeh Baghban (University of Social Welfare and Rehabilitation Sciences, 2021)
Objective Moral distress may occur when people are unable to follow professional standards and ethical values in their profession. It is a significant issue in the healthcare profession and has negative consequences. In addition, there is a concern that it may adversely affect clinical performance and, in some cases, patient outcomes. Based on the evidence, occupational therapists experience moral distress, Therefore, there is a need for a tool that enables researchers to identify the extent of moral distress in each individual and to measure the effectiveness of strategies designed to reduce distress and prevent employee burnout. The aim of this study was to develop and evaluate the face and content validity of the Moral Distress Questionnaire in occupational therapists. Materials & Methods This psychometric study was performed in two stages. The first stage involved preparing a pool of questionnaire items, and the second stage examined the face and content validity of the questionnaire. First, texts and related studies were reviewed to extract the questionnaire items. Searching various databases was done to find any conditions that create moral distress in occupational therapy. Three qualitative studies conducted in the field of ethical issues of occupational therapists in the field of psychiatry, children and adults were fully studied. The codes extracted from these studies and the quotations of the interviewees were read. Then the questionnaire items were extracted from the codes, sentences and phrases of the studies. The items were read several times and edited in terms of content clarity, grammar and concept comprehension, and duplicate topics were removed. After preparing the pool of items for the preliminary questionnaire, the scientific stages of face and content validity of the questionnaire were completed. The face validity of the questionnaire was measured qualitatively and quantitatively by 30 occupational therapists who were selected by available sampling from clinics, hospitals and public and private centers. Inclusion criteria were at least one year of work experience in various fields of occupational therapy. Quantitative face validity was performed by determining the impact score of the item. In order to perform qualitative content validity, experts in the field of teaching ethics in occupational therapy and familiar with tool development were invited to review the questionnaire and exchange views in a face-to-face meeting. Seven people participated in the panel of experts. Participants were told that the tool would be an Evaluative tool designed to assess the extent of moral distress among occupational therapists working in clinical settings. After carefully studying the tool, they were asked to consider and comment on the four criteria of clarity, simplicity, transparency, and relevance of items to moral distress. To assess the quantitative content validity of the questionnaire, 20 occupational therapists with doctoral degrees were asked to complete the relevant forms for assessing Content Validity Ratio (CVR) and Content Validity Index (CVI). Results After reviewing the texts and related studies and analyzing the findings and concepts, a preliminary questionnaire with 50 items was extracted. The items of the questionnaire reached 22 items after completing qualitative and quantitative face and content validity. The impact score of the item was between 2.85 to 4.83. The CVR was in the acceptable range of 0.5 to 1 with an average of 0.7. The CVI of the questionnaire was 0.93. Conclusion The Moral Distress Questionnaire in Occupational Therapists with 22 items on a four-point scoring scale has appropriate content validity and can be used to measure moral distress in occupational therapists after completing the validity and reliability steps.